Facilitating effects of the reductive soil disinfestation process combined with Paenibacillus sp. amendment on soil health and physiological properties of Momordica charantia - Liu, Liangliang; Xie, Yi; Zhong, Xin; Deng, Quanquan; Shao, Qin; Cai, Zucong; Huang, Xinqi (Frontiers in Plant Science, 2023)
Reductive soil disinfestation (RSD) is an anaerobic and facultative anaerobic microbial-mediated soil management process. The extent of improvement of diseased soil properties by RSD relative to comparable healthy soil is, however, not well characterized. Importantly, how to promote the colonization efficiency of these facultative anaerobic functional species to ensure soil and plant health remain unknown. Here, Fusarium wilt-diseased soil of Momordica charantia grown under a plastic-shed field (PS-CK) was used to conduct molasses-RSD (MO-RSD) along with Paenibacillus sp. (a model of facultative anaerobic species) (MOPA-RSD) treatment, and the soil from a nearby open-air paddy field was considered comparable healthy soil (OA-CK). Both RSD treatments significantly improved the properties of PS-CK soil, and the extent of improvement of soil pH, Fusarium oxysporum reduction efficiency (98.36% 99.56%), and microbial community and functional composition were higher than that achieved for OA-CK soil, which indicated that RSD-regulated most soil properties outperformed those of the comparable healthy soil. The disease incidence and ascorbic acid content of M. charantia in MO-RSD- and MOPA-RSD-treated soils were considerably decreased, while the weight and soluble protein contents were correspondingly increased, as compared to those of M. charantia in PS-CK soil. Specifically, the changes in these physiological properties of M. charantia in MOPA-RSD soil performed well than that in MO-RSD soil. The relative abundances of Cohnella, Effusibacillus, Rummeliibacillus, Oxobacter, Thermicanus, and Penicillium enriched in both RSD-treated soils were positively correlated with Paenibacillus and negatively correlated with F. oxysporum population and disease incidence (P < 0.05). Notably, the relative abundances of these potential probiotics were considerably higher in MOPA-RSD-treated soil than in MO-RSD alone-treated soil. These results show that the RSD process with inoculation of Paenibacillus sp. could promote the colonization of this species and simultaneously stimulate the proliferation of other probiotic consortia to further enhance soil health and plant disease resistance.